Strategi Guru dalam Mengatasi Kesulitan Membaca Siswa Kelas III: Studi Kasus SD Negeri di Kecamatan Tarogong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the low reading ability of elementary school students, particularly in reading comprehension, which is influenced by limited vocabulary, the use of local languages, the impact of post-pandemic learning conditions, and a lack of parental support. The study aims to analyze teachers’ strategies for addressing reading difficulties among third-grade students in a public elementary school in Tarogong District. The method used is a qualitative approach with a case study design. The research subjects include teachers and third-grade students selected through purposive sampling. Data were collected through observation, interviews, and documentation, while data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing, with validity ensured through triangulation. The results show that students’ reading abilities are uneven, mainly due to the impact of the pandemic and minimal learning support at home. The strategies implemented by teachers include intensive and continuous guided instruction, remedial teaching, and additional learning hours. In addition, motivational and emotional approaches such as providing attention, encouragement, and rewards have also been proven to increase students’ interest, confidence, and engagement in reading activities. Thus, adaptive, consistent, and student-centered strategies are effective in improving students’ reading ability.